Industrial radiotracer application in flow rate measurement and flowmeter calibration using ⁹⁹mTc and ¹⁹⁸Au nanoparticles radioisotope - Mohd Yunus, Mohd Amirul Syafiq; Hussain, Siti Aslina; Sipaun, Susan Maria (Elsevier, 2019)
The flow rate or fluid velocity measurement is important to maintain fluid flow quality performance in the systems. This study focuses on determination of volumetric flow rate measurement and to calibrate the conventional flowmeter using industrial radiotracer approach in quadrilateral gas-liquid bubble column reactor. In this work, two different radioisotopes which emit γ-ray have been chosen as radioactive tracer which is 99mTc produced from 99Mo/99mTc radioisotope generator and 198Au nanoparticle form neutron activation at research nuclear reactor TRIGA Mark II. Both radioisotopes representing liquid and solid tracer purposely designed for tracing liquid flow. The peak to peak radiotracer method known as pulse velocity method was applied to determine the volumetric flow rate. The radiation signals were monitored using 4 unit NaI scintillation detectors located at 4 different points nearby the inlet and outlet of the quadrilateral bubble column reactor process stream. The water volume inside the bubble column reactor was fixed at 0.04 m3 and liquid flow rates in this reactor were specified on installed flowmeter at different reference value which is 4 lpm, 8 lpm, and 12 lpm, respectively. The experimental result shows very good linearity and repeatability by following the theoretical equations with less uncertainty in volumetric flow rate measurement. The obtained results also validated the effectiveness of the proposed method for the installed flowmeter calibration efficiency.